The Drosophila Pericentrin-like-protein (PLP) cooperates with Cnn to maintain the integrity of the outer PCM - Jennifer H. Richens; Teresa P. Barros; Eliana P. Lucas; Nina Peel; David Miguel Susano Pinto; Alan Wainman; Jordan W. Raff (Biology Open, 2015)
Centrosomes comprise a pair of centrioles surrounded by a matrix of pericentriolar material (PCM). In vertebrate cells, Pericentrin plays an important part in mitotic PCM assembly, but the Drosophila Pericentrin-like protein (PLP) appears to have a more minor role in mitotic fly cells. Here we investigate the function of PLP during the rapid mitotic cycles of the early Drosophila embryo. Unexpectedly, we find that PLP is specifically enriched in the outer-most regions of the PCM, where it largely co-localizes with the PCM scaffold protein Cnn. In the absence of PLP the outer PCM appears to be structurally weakened, and it rapidly disperses along the centrosomal microtubules (MTs). As a result, centrosomal MTs are subtly disorganized in embryos lacking PLP, although mitosis is largely unperturbed and these embryos develop and hatch at near-normal rates. Y2H analysis reveals that PLP can potentially form multiple interactions with itself and with the PCM recruiting proteins Asl, Spd-2 and Cnn. A deletion analysis suggests that PLP participates in a complex network of interactions that ultimately help to strengthen the PCM.